Changes in Seed and Leaf Characteristics of Common Bean (Phaseolus vulgaris L.) Cultivars Treated With Co-60 - BOZOGLU, HATICE; OZCELIK, HUSEYIN; PEKSEN, ERKUT (Asian Journal of Chemistry, 2010)
The aim of this study was to create a variation in bean which is an important plant Black sea region of Turkey by using physical mutation and to introduce a plant material which can complete the deficient characteristics of cultivars are grown in this region. Four cultivars were used in this study. Different Co-60 γ-rays (50, 100, 200, 300 Gy doses) were used as mutation source. The influences of γ-irradiation on leaf and grain characteristics of cultivars were investigated in M2 population. Higher variation coefficients were obtained in doses of 50, 100, 200, 300 Gy compared to control group, but mutant plant count was lower for 300 Gy dose due to this dose's higher influence. For this reason, variation coefficients were found lower compared to control. It was determined that mutagen application with different doses in different cultivars created variation in various seed and leaf characteristics of bean. According to t-test results, change of seed characters was lower than leaf characters.